2015
DOI: 10.7150/jca.11228
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of GOLPH3 is Associated with the Proliferation of Prostate Cancer

Abstract: Background: Golgi phosphoprotein 3 (GOLPH3) is a metastasis-associated gene, however its role in cell proliferation of prostate cancer (PCa) has not yet been elucidated.Methods: The level of expression of GOLPH3 and other genes was examined by quantitative real-time PCR (QPCR) and western blot analysis. Furthermore, we performed a comprehensive analysis of the expression of GOLPH3 in PCa using a tissue microarray (TMA) and correlated our findings with pathological parameters of PCa. RNA interference (RNAi) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…In the current study, moderate/intense cytoplasmic expression of GOLPH3 protein was found in 25% of BPH and in 68.4% of PC tissues and the difference was statistically significant. This result was similar to a previous study that reported 30% positivity in BPH and 64% in PC samples [ 28 ] but higher than previous studies that detected moderate/intense GOLPH3 expression in 5% of BPH, 8% of HGPIN and 37-40.66% of PC [ 8 , 11 ]. Therefore, differences noted in the expression of GOLPH3 in PC compared with BPH and PIN may facilitate the clinical diagnoses of PC.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, moderate/intense cytoplasmic expression of GOLPH3 protein was found in 25% of BPH and in 68.4% of PC tissues and the difference was statistically significant. This result was similar to a previous study that reported 30% positivity in BPH and 64% in PC samples [ 28 ] but higher than previous studies that detected moderate/intense GOLPH3 expression in 5% of BPH, 8% of HGPIN and 37-40.66% of PC [ 8 , 11 ]. Therefore, differences noted in the expression of GOLPH3 in PC compared with BPH and PIN may facilitate the clinical diagnoses of PC.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to a previous study in castration-resistant PC, GOLPH3 expression was positively correlated with Gleason score, tumor stage and lymph node metastasis [ 11 ]. On the contrary, no significant associations were found with Gleason score or tumor stage [ 28 ]. Collectively, these observations suggest that GOLPH3 acts as an oncogene in PC and may be a useful target for therapeutic interventions [ 11 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of papers has shown that GOLPH3 drives cancer in several other solid tumors such as Neuroblastoma (NB) [42], Non-Small Cell Lung Cancer (NSLC) [89], epithelial ovarian carcinoma [90], prostate cancer [91,92], gastric cancer [93], and hepatocellular carcinoma [94,95] ( Figure 2). Recent reports indicate that GOLPH3 overexpression can be used as a positive biomarker for tumor progression and poor survival in these cancer types [89][90][91][92][93][94][95][96][97][98]. Experimental data in cancer cell lines or in nude mice revealed the role of GOLPH3 in cell proliferation, metastasis formation and angiogenesis ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer, miR-186 repressed cell proliferation via targeting YY1 and CDK6 (23) or GOLPH3 (22). Downregulation of GOLPH3 enhanced p21 expression and repressed the expression of Cyclin B1 and CDK1/2, thus blocking G1/S transition (73). MiR-186 repressed invasion and migration of prostate cancer cells by targeting Twist 1 (24).…”
Section: Mir-186 As a Tumor Suppressor Mirnamentioning
confidence: 99%